Aktivitas Antioksidan dan Evaluasi Fisik Sediaan Body Scrub dari Bubur Rumput Laut Boergesenia forbesii dan Serbuk Kencur (Kaempferia galanga) - Rini Yanuarti; Nurfitriyana Nurfitriyana; Ginanjar Pratama; Muhammad Zuhriyanto (Jurnal FishtecH, 2022)
Seaweed has bioactive components that are very much needed in cosmetic preparations, in addition to seaweed, natural ingredients that can be used are kencur (Kaempferia galanga). This study aims to determine the best combination of B. forbesii seaweed porridge and kencur (K. galanga) powder as a body scrub preparation from the results of antioxidant activity and physical evaluation. This research was conducted by looking at the difference in concentration between B. forbesii and kencur (K. galanga) seaweed with a ratio of 1:1 (R1 cream), 1:2 (R2 cream), and 2:1 (R3 cream) and without the addition of seaweed. and Moringa (R0). The cream preparation was then tested for antioxidants and physical evaluation of the preparation included pH, homogeneity, centrifugal test, and organoleptic observations. The test results showed that all formulations of body scrub cream which were given B. forbesii seaweed porridge and kencur (K. galanga) powder had weak antioxidant activity. The results of the evaluation of physical preparations showed good results for the skin, but the formulation of R2 cream which is the best cream seen from the overall evaluation results